Construction of Legal Responsibility Regulations for Notaries and Notary Employees If Notary Employees Commit Unlawful Acts - Rizgi, Ahmad; Istislam; Wisnuwardhani, Dyah Aju (The Islamic Education and Multiculturalism Foundation, 2024)
When examined from an empirical/sociological approach, several issues arise within the notarial profession. Notaries generally have good (close) relationships with their employees. However, it is not uncommon for notary employees to commit fraud behind the notary's desk, either directly or indirectly. On the part of the notary, it is also possible that the notary covers up various mistakes made by their employees in order to maintain credibility and other such reasons. Such unlawful acts will be dealt with both under the law and the Notary Code of Ethics. It is known that notary employees have a legal relationship with the notary based on the work performed by the notary. There is a need for legal construction from upstream to downstream concerning the legal status/relationship and legal responsibilities of both notaries and notary employees. This is aimed at ensuring that each party has a legal reference as to the extent to which legal actions can be considered violations or not. The legal vacuum in regulating the relationship between notaries and their employees when committing unlawful acts increases the possibility of legal violations.